THE IDENTITY OF SOME BURMAN SPECIES - a. j. g. h. kostermans (REINWARDTIA, 1969)
Burman (Thesaurus zeylanicus, 1737) depicted on tab. 79 Nux Moschata, spuria, sylvestris, Caryophylli arboris, oppositis, Nobis.The plate depicts a sterile branch with conspicuous, stalked, perulateleaf buds. The local name is given as Iryaghedhi (cited from Mus. Zeyl.,p. 58). Linnaeus edumerated the species in Fl. Zeyl., p. 590 under "Barbarae Annihilatae".